Model Manajemen MTs NU Banat Kudus Dalam Meningkatkan Mutu Pendidikan Islam - Nailissa'adah Nailissa'adah (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2017)
Abstract This research answers: (1) How can governance of MTs NU Banat Kudus?; (2) How does the strategy of increasing the quality of Islamic education in MTs NU Banat Kudus?; and (3) How does the management model of MTs NU Banat Kudus in enhancing the quality of Islamic education? This research is a field research with a qualitative approach by interviews, observation and documentation. Analysis of data using model analysis Miles and Huberman by step data collection, data reduction and data display, then the conclusion and verification. The results showed that: 1) the governance of MTs NU Banat Kudus are human resources management, student affairs, curriculum, facilities, finance, administration and public relations; 2) The strategies are developed the professionalism of teachers and employees, additional hour, open class dormitory, complete learning facilities, streamline coordination, cooperation, provide reinforcement religiosity, maintaining environmental conduciveness and held a debriefing after study. 3) The management model of MTs NU Banat Kudus is TQM model with emphasis on customer satisfaction, continue to make improvements that are sustainable, obsessed on the quality, the teamwork, optimizing the role of leader and always empowering employees. Keywords: Management Model, MTs NU Banat Kudus, Islamic Education  Quality.  Abstrak Rumusan masalah penelitian ini: (1) Bagaimana tata kelola MTs NU Banat Kudus?; (2) Bagaimana strategi peningkatan mutu pendidikan Islam di MTs NU Banat Kudus?; dan (3) Bagaimana model manajemen MTs NU Banat Kudus dalam meningkatkan mutu pendidikan Islam? Penelitian ini adalah penelitian lapangan kualitatif. Data dikumpulkan melalui wawancara, observasi dan dokumentasi. Analisis data dengan model Miles and Huberman dari pengumpulan data, reduksi data, display data serta kesimpulan dan verifikasi. Hasil penelitian: 1) tata kelola MTs NU Banat Kudus yaitu manajemen SDM, kesiswaan, kurikulum, sarana prasarana, keuangan, ketatausahaan, dan humas; 2) Strateginya dengan mengembangkan profesionalisme guru/karyawan, jam tambahan, kelas asrama, melengkapi fasilitas, koordinasi, kerjasama, religiusisme, mengkondusifkan lingkungan, dan pendidikan pascabelajar; 3) Model manajemennya model Total Quality Management (TQM) mengutamakan kepuasan pelanggan, perbaikan berkesinambungan, berobsesi kualitas, kerjasama tim, mengoptimalkan kepemimpinan serta memberdayakan karyawan. Kata Kunci: Model Manajemen, MTs NU Banat Kudus, Mutu Pendidikan Islam.